AUTOMATED FLOW-INJECTION SERIAL DYNAMIC DIALYSIS TECHNIQUE IN THE STUDY OF DRUG-BINDING WITH CYCLODEXTRINS - Sideris, EE; Georgiou, C.A.; Koupparis, MA; Macheras, PE (ANALYTICA CHIMICA ACTA, 1994)
A flow-injection dynamic dialysis technique is presented for the determination of binding parameters of drugs to cyclodextrins (CDs). The automated system consists of a flow-injection unit, the sample loop of which is the receiving compartment of a dialyser unit, and a home made timing module for operation control through two flow switching solenoid valves. The procedure of binding studies is rapid and yields reproducible results. Binding parameters of CD-micromolecule complexes was calculated using the Scatchard model. Typical examples of the binding of p-nitrophenol with alpha-CD(K-as=1.56x10(3) M(-1) at pH 7.4 and 2.06x10(3) M(-1) at pH 9.0), salicylic acid with beta-CD (K-as=3.8 x 10(2) M(-1) at pH 1.5 and 51 M(-1) at pH 7.4) and ibuprofen with beta-CD (K-as=2.2x10(2) M(-1) at pH 2.5) are presented and the binding constants obtained are compared to literature values. 1:1 stoichiometry was found in all cases and within run precision ranged from 2 to 14% R.S.D. The between run precision for the binding of p-nitrophenol to alpha-CD was 2% (n=3).
Keywords: AUTOMATED SERIAL DYNAMIC DIALYSIS TECHNIQUE; cyclodextrins; DRUG BINDING TO CYCLODEXTRINS; FLOW INJECTION; Ibuprofen; P-NITROPHENOL; SALICYLIC ACID; Scatchard model